Comparative analysis of dietary vs. non-dietary approaches in obesity and disordered eating behaviors: a narrative review of the literature - Chiara Breda; Adriana Chiarelli; Giulia Quarantelli; Maria Vittoria Conti; Nagaia Madini; Hellas Cena (Eating and Weight Disorders)
Abstract Purpose This narrative review aims to conduct a comparative analysis of dietary and non-dietary approaches in the management of weight and disordered eating behaviors (DEBs) in adults with obesity. Methods Studies were identified from Medline (PubMed), including only English-language manuscripts published from 1998 to 2024. To be included in the review the studies had to be RCTs that compared the effect of dietary and non-dietary approaches on weight loss and DEBs in adults with obesity not being treated with pharmacological treatments. Results Seven randomized controlled trials (RCTs) reported in 8 manuscripts published between 1998 and 2024 met the inclusion criteria. The sample size ranged from a minimum of 16 subjects to a maximum of 219. All studies involved adult subjects, mainly women, with first-, second-, or third-degree obesity and most subjects had cognitive restriction and/or uncontrolled eating. Dietary approaches were characterized by moderate caloric restriction (CR) and restriction of fat intake. In contrast, non-dietary approaches focused on mindful eating (ME), intuitive eating (IE) and weight neutral (WN) approaches. Of the 7 RCTs included, 5 reported greater weight loss in the diet group compared to the non-diet group; however, only one of these sustained the result at follow-up. In contrast, 4 studies demonstrated greater improvements in DEBs in the non-diet group. Conclusion CR is essential for weight loss in individuals with obesity, but long-term weight management also hinges on their relationship with food. The psychological improvements reported in non-dietary versus dietary approaches should not be overlooked and can be a starting point for the development of multidisciplinary interventions involving synergistic actions between diet, exercise, and practices to improve DEBs with the goal of reducing the obesity epidemic. Level of evidence Level I, at least one properly designed randomized controlled trials; systematic reviews and meta-analyses; experimental studies.